Behaviour of piozoelectric devices embedded in bone cement - Frias, C. (2011)
Bone cements based on polymethacrylate (PMMA) are essential products in joint arthroplasty. PMMA bone cement function is to locate the implants components in the body skeleton, load transition through the joint into the bone and muscle surrounding for a very for a very long period of time. Its mechanical properties are well established in the literature. Since bone cement fills the void between the prosthesis (polymer or metallic) and bone, it is subjected to high stress and has to operate in a relatively aggressive environment, like human body. Therefore, based on surrounding environment PMMA bone cements application, this material has specific mechanical properties that enhance a good performance in this condition. These stresses are mainly measured indirectly with non-invasive methods. In-situ measurements would be more interesting to really understand and quantify these stresses. Piezoelectric devices are an interesting way to measure forces in difficult accessibility environment, since they are self-power, i. e., they are able to generate an electric signal by converting mechanical energy into electrics with no need for power supply. When embedded in bone cement one expects to be able to analyze the health structure in real-time. Positioning of the sensing device is a critical factor worthy of a thorough study in order to understand its behavior to surroundings.